MANAGEMENT OF CHARACTER EDUCATION STRENGTHENING PROGRAMS IN ELEMENTARY SCHOOLS - Kappey Laiv (Sensei International Journal of Education and Linguistic, 2022)
The purpose of this study is to describe the management of character education strengthening programs in elementary schools. The type of research used is case study research using a qualitative approach. Data collection techniques used in the form of observation, interviews, and documentation. The stages of data analysis use three steps, namely: data condensation, presenting data, and drawing conclusions. The conclusions of this research show: (1) the planning of the character education strengthening program has several stages, namely observation, coordination meetings, compiling work programs, program implementation, monitoring, and evaluation, (2) the school principal is assisted by the school development team and school coordinator, ( 3) implementation of the program through four stages of activity, namely integration, acculturation, exemplary, and collaboration with parents.